Pengaruh Media Electric Big Book Untuk Meningkatkan Kemampuan Berbicara Anak Usia 5-6 Tahun Di Ra El Haqqa Quraniq School Pekanbaru - Balqiah, Hasanah; Kurnia, Rita; Zulkifli, Zulkifli (Innovative: Journal Of Social Science Research, 2024)
Based on observations at Ra El Haqqa Quranic School Pekanbaru, it was found that learning activities to improve speaking skills were found to have problems at the age of 5-6 years, so that alternative media was needed, namely the electric big book. This research aims to determine the effect of improving the speaking skills of children aged 5-6 years before and after being given treatment in the form of interactive media electric big book at Ra El Haqqa Quraniq School Pekanbaru. This type of research is a quantitative experiment with a pretest-posttest design. The population in this study were Ra El Haqqa Quraniq School Pekanbaru children aged 5-6 years, namely 11 children using saturated sampling. Based on data analysis and percentage results, there is a significant influence. The data collection technique carried out by the researcher was observation, data analysis using the t-test using SPSS ver 29. The results of the research showed that there was an increase in speaking ability with the electric big book media seen from the average score obtained before treatment and after treatment. The pretest research results obtained a percentage result of 28.334% and the posttest results obtained a percentage result of 81.25%. Based on the research results, it can be concluded that the electric big book media is suitable and effective for use as a learning medium and improves speaking skills in children aged 5-6 years at Ra El Haqqa Quranic School.